Sputtering target material and method for manufacturing sputtering target material

By preparing KNN sintered bodies with low density and moderate hardness, and controlling the temperature during oxidation treatment, the problem of easy rupture of KNN targets during production and use is solved, and the preparation of low-density and crack-resistant targets and high-quality KNN films is achieved.

CN119731367APending Publication Date: 2025-03-28SUMITOMO CHEM CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062783.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing KNN targets are prone to rupture and notch problems during production and use, and it is difficult to maintain low density during oxidation treatment and have high mechanical strength.

Method used

By preparing a KNN sintered body with a density of 4.2 g/cm3 or less, a Vickers hardness of 30 or more and a minimum area of ​​200 or less, and an average area particle size of 3.0 μm or more, a low-temperature and low-pressure hot-pressure sintering method is adopted, and the heating temperature is controlled to be low in the oxidation treatment to ensure the low density and crack resistance of the target material.

Benefits of technology

A low-density and crack-resistant KNN target material is achieved, ensuring that cracking and notch are not easily generated during production and use, and a KNN film with specified physical properties and characteristics can be reliably obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731367A_ABST
    Figure CN119731367A_ABST
Patent Text Reader

Abstract

Provided is a sputtering target comprising a sintered body of an oxide containing potassium, sodium, niobium, and oxygen, the sputtering target having a density of 4.2 g / cm3 or less, a Vickers hardness of 30-200, and an area average particle diameter of a plurality of crystal grains observed on a sputtering surface of 3.0 [mu] m or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sputtering target and a method for manufacturing the sputtering target. Background Art

[0002] As a material for manufacturing a piezoelectric film, a sputtering target made of a sintered body containing oxides of potassium, sodium, niobium, and oxygen (hereinafter also referred to as a KNN target or simply a target) is sometimes used (see, for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-146623 Summary of the invention

[0006] Problems to be solved by the invention

[0007] An object of the present invention is to provide a low-density and crack-resistant KNN target.

[0008] Means for solving problems

[0009] According to one embodiment of the present invention,

[0010] Provided is a sputtering target material, which is composed of a sintered body containing oxides of potassium, sodium, niobium and oxygen.

[0011] Density: 4.2g / cm 3 the following,

[0012] Vickers hardness is 30 or more and 200 or less,

[0013] The area average grain size of a plurality of crystal grains observed on the sputtered surface was 3.0 μm or more.

[0014] According to another aspect of the present invention, there is provided a method for manufacturing a sputtering target material, the method comprising:

[0015] (a) a step of mixing a raw material powder containing a compound including sodium and a raw material powder containing a compound including niobium at a predetermined ratio, and heating the mixture in an oxygen-containing atmosphere to produce a calcined powder containing sodium and niobium;

[0016] (b) a step of mixing a raw material powder containing a compound including potassium and a raw material powder containing a compound including niobium at a predetermined ratio, and heating the mixture in an oxygen-containing atmosphere to produce a calcined powder containing potassium and niobium;

[0017] (c) a step of mixing the calcined powder prepared in (a) and the calcined powder prepared in (b) at a predetermined ratio, and heating (calcining) the mixture in an oxygen-containing atmosphere to prepare a raw material powder containing potassium, sodium and niobium; and

[0018] (d) a step of applying a predetermined pressure to the calcined powder produced in (c) to form a green compact, and heating the green compact to form a sintered body.

[0019] The heating temperature in (a) is made higher than the heating temperature in (b).

[0020] Effects of the Invention

[0021] According to the present invention, a KNN target material having a low density and being resistant to cracking can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a diagram showing one embodiment of the target material of the present invention.

[0023] Figure 2 This is a schematic diagram of the structure of a sintering device used in the present invention.

[0024] Figure 3 (a) is a schematic diagram of the cross section of sample 1. Figure 3 (b) is a photograph of the fracture surface of sample 1.

[0025] Figure 4 (a) is a schematic diagram of the cross section of sample 21. Figure 4 (b) is a photograph of the fracture surface of sample 21. DETAILED DESCRIPTION

[0026] <Insights Obtained by the Inventors>

[0027] KNN targets (KNN sintered bodies) are usually produced by a sintering process using a so-called hot pressing method (hereinafter also referred to as "hot pressing sintering"), that is, a sintered powder (KNN sintered powder) containing potassium (K), sodium (Na), niobium (Nb) and oxygen (O) is subjected to mechanical pressure to form a compact, and the compact is heated to sinter it. This is because KNN is a difficult-to-sinter material, so in order to promote the sintering (sintering reaction) of the KNN sintered powder during sintering under normal pressure, it is necessary to sinter at a very high temperature.

[0028] However, in order to avoid burning of furnace components such as heaters and insulating materials, hot pressing sintering is usually carried out in a nitrogen atmosphere, an inert gas atmosphere (for example, an atmosphere containing inert gases such as argon and helium), or a vacuum atmosphere, and the oxygen partial pressure in the atmosphere cannot be increased. Therefore, if hot pressing sintering is performed, part of the O in the KNN sintered powder is detached. As a result, there are cases where the composition of the final KNN target deviates from the desired composition. For example, there are cases where the composition of O in the final KNN target is less than the desired composition. If a KNN target with such a deviated composition is used for sputtering film formation, the composition of the resulting sputtered film (KNN film) also deviates from the desired composition, and as a result, there are cases where the characteristics of the KNN film are reduced. For example, there are cases where the insulation of the KNN film is reduced and the leakage current becomes larger.

[0029] Therefore, the KNN target (KNN sintered body) produced by hot pressing sintering is subjected to heat treatment (oxidation treatment) in an atmosphere containing O. Thus, O is introduced into the KNN target from which a part of O is released by hot pressing sintering, and the final KNN target can have a desired composition.

[0030] In addition, the KNN target is required to be not prone to cracks, notches, etc., whether in the production of the KNN target (for example, in the implementation of the above-mentioned oxidation treatment, in the mechanical processing such as grinding when the KNN target is produced), or in the sputtering film formation using the KNN target. It should be noted that in this specification, KNN targets that are not prone to cracks, notches, etc. are also referred to as targets with high mechanical strength. Previously, in order to improve the mechanical strength of the KNN target, it was considered that the KNN target should be made into a high density. Therefore, hot pressing sintering was used to produce high-density KNN targets.

[0031] However, when the above-mentioned oxidation treatment is performed on a high-density KNN target, in order to fully introduce O into the center of the KNN target and fully oxidize it to the center, the heating temperature in the oxidation treatment needs to be high temperature (for example, higher than 1100°C). Therefore, it is easy for the KNN target to warp and crack, and the production yield of the KNN target is reduced. In addition, when the heating temperature in the oxidation treatment is high temperature, during the implementation of the oxidation treatment, K in a part of the KNN target is easy to scatter (volatize). Therefore, there are still cases where the composition of the final KNN target deviates from the required composition. For example, there are cases where the composition of K in the final KNN target is less than the required composition.

[0032] Therefore, it is also considered to produce a low-density KNN target by hot pressing sintering under low temperature and low pressure conditions. When the low-density KNN target is subjected to oxidation treatment, even if the heating temperature in the oxidation treatment is low, O can be fully introduced into the center of the KNN target and fully oxidized to the center. In addition, by making the heating temperature in the oxidation treatment low, it is not easy to cause warping and cracking in the KNN target during the implementation of the oxidation treatment, and it is possible to suppress the volatilization of K in a part of the KNN target.

[0033] However, the mechanical strength of a low-density KNN target is likely to be lower than that of a high-density KNN target. Therefore, a low-density KNN target is likely to be cracked or chipped during the production of the KNN target or during sputtering film formation.

[0034] The inventors of the present invention have conducted in-depth research on the above-mentioned subject. As a result, the following insight is obtained, that is, by setting the Vickers hardness within a specified range and setting the area average particle size of multiple grains observed in the surface of the KNN target that becomes the sputtering surface to a specified value or more, a crack-resistant KNN target can be obtained even at a low density. That is, it is found that a KNN target can be obtained, although it is a low-density KNN target, it is not easy to produce cracks, notches, etc. in the production of the KNN target and in the sputtering film.

[0035] The present invention has been accomplished based on the above-mentioned problems and findings obtained by the inventors.

[0036] <One embodiment of the present invention>

[0037] Hereinafter, one embodiment of the present invention will be described with reference mainly to Figure 1 , Figure 2 .

[0038] (1) Composition of target material

[0039] The target material 10 of this embodiment is mainly composed of a sintered body containing an oxide (alkali niobium oxide) containing K, Na, Nb and O, that is, a KNN sintered body. The crystal grains that constitute the target material 10 mainly have a perovskite structure. Specifically, the target material 10 has a composition formula (K 1-x Na x )NbO 3(0<x<1) indicates that the coefficient x [=Na / (K+Na)] in the above composition formula is 0<x<1, preferably 0.4≤x≤0.8. The KNN sintered body constituting the target 10 is an oxide sintered body substantially composed of K, Na, Nb and O, or an oxide sintered body further containing the dopant elements shown below. Here, the term "substantially" means that more than 99% of all atoms constituting the target 10 are composed of K, Na, Nb and O, or when the target 10 contains a dopant element, it means that it is composed of K, Na, Nb, O and the dopant element.

[0040] The composition of K, Na, and Nb in the target 10 (([K]+[Na]) / [Nb]) is greater than 1.0, preferably 1.02 or more, and preferably 1.10 or less, more preferably 1.07 or less, and further preferably 1.04 or less.

[0041] Here, [K], [Na], and [Nb] in the formula of ([K] + [Na]) / [Nb] are the molar number of K atoms, the molar number of Na atoms, and the molar number of Nb atoms in the target material 10, respectively. The composition of the target material 10 can be obtained, for example, by atomic absorption spectrometry (AAS) and inductively coupled plasma emission spectrometry (ICP-AES). That is, the molar number of K atoms and the molar number of Na atoms are obtained by AAS (e.g., Z-2310 manufactured by Hitachi High Technologies Co., Ltd.), and the molar number of Nb atoms are obtained by ICP-AES (e.g., SPS5000 manufactured by Seiko Instruments Co., Ltd.). Thus, the composition of the target material 10 can be obtained. It should be noted that, although it is also conceivable to determine the molar number of K atoms and the molar number of Na atoms by using only ICP-AES or only energy dispersive X-ray spectroscopy (EDX), the reliability of the measurement results is reduced due to low measurement sensitivity and lack of reproducibility.

[0042] In the target material 10, at least one element (dopant) selected from Cu and Mn is sometimes added at a concentration of 0.1 at% to 2.0 at% inclusive. When both elements Cu and Mn are added, the total concentration is 0.1 at% to 2.0 at%. Thus, the KNN film formed by sputtering using the target material 10 can contain at least one element selected from Cu and Mn at a predetermined concentration.

[0043] It should be noted that the term “adding at least one element selected from Cu and Mn in the target material 10 at a concentration of 0.1 at % to 2.0 at %” in this specification means adding Cu and Mn elements in such a manner that the value of the ratio of the total number of Cu and Mn atoms to the total number of atoms of all elements constituting the target material 10 (= {(number of Cu atoms + number of Mn atoms) / (number of K atoms + number of Na atoms + number of Nb atoms + number of Cu atoms + number of Mn atoms)}×100) is 0.1 to 2.0.

[0044] The target material 10 is formed into a disk shape, for example, and is bonded (laminated) to a backing plate (not shown) made of Cu or the like via a bonding material including indium (In), tin (Sn), or an alloy including any of these metals, and is used as a sputtering target. Of the two main surfaces of the target material 10, the surface other than the bonding surface with the backing plate is used as a surface exposed to plasma such as argon (Ar) during film formation, that is, as a sputtering surface 10s that releases atoms constituting the sputtered film (KNN film).

[0045] When the target 10 is disc-shaped, the diameter of the main surface of the target 10, preferably the diameter of the sputtering surface 10s, is, for example, 30 mm or more, preferably 75 mm or more, more preferably 90 mm or more, further preferably 100 mm or more, and particularly preferably 200 mm or more. The area of ​​the main surface of the target 10, preferably the area of ​​the sputtering surface 10s, is, for example, 4500 mm 2 Above, preferably 5000mm 2 More than 6000mm 2 More preferably, 7500 mm 2 Above, particularly preferably 15000mm 2 It should be noted that the upper limits of the diameter of the main surface of the target material 10 and the area of ​​the main surface of the target material 10 are not particularly limited.

[0046] The target 10 may also be a plate having a rectangular main surface. The length of the long side direction of the main surface of the target 10, preferably the length of the long side direction of the sputtering surface 10s, is, for example, 80 mm or more, more preferably 100 mm or more, further preferably 120 mm or more, further preferably 150 mm or more, and particularly preferably 200 mm or more. The length of the short side direction of the main surface of the target 10, preferably the length of the short side direction of the sputtering surface 10s, is, for example, 50 mm or more, more preferably 80 mm or more, further preferably 100 mm or more. The area of ​​the main surface of the target 10, preferably the area of ​​the sputtering surface 10s, is, for example, 4500 mm. 2 Above, preferably 5000mm 2 More than 6000mm 2More than 7500mm is more preferred 2 Above, particularly preferably 15000mm 2 It should be noted that the upper limits of the lengths in the long-side direction and the short-side direction of the main surface of the target 10 and the area of ​​the main surface of the target 10 are not particularly limited.

[0047] The thickness of the target material 10 is, for example, 2 mm or more, preferably 3 mm or more, more preferably 5 mm or more, further preferably 7.5 mm or more, and is preferably 25 mm or less, more preferably 20 mm or less, further preferably 15 mm or less.

[0048] The backing plate is made of a conductive material, such as a metal or an alloy thereof, and examples thereof include Cu, Cu alloys, aluminum (Al), Al alloys, titanium (Ti), stainless steel (SUS), etc. The size of the backing plate is not particularly limited as long as it can be bonded to and support the target 10, can be mounted in a sputtering device, and can function as a cooling plate for the target 10 and a sputtering electrode.

[0049] Here, in this specification, the so-called "crack-resistant target 10" means a target 10 that is not prone to cracks, chips, etc. during the production of the target 10 (for example, during the implementation of the oxidation treatment described later, during the implementation of mechanical processing such as grinding), or a target 10 that is not prone to cracks (cracks) that may cause abnormal discharge during sputtering film formation using the target 10. It should be noted that, in general, it is considered that a low-density target is not resistant to cracks, and cracks, chips, etc. are easily generated during the production of the target 10 and during sputtering film formation.

[0050] The target material 10 of this embodiment has all of the following three characteristics: a density of 4.2 g / cm 3 The following characteristics: Vickers hardness is 30 or more and 200 or less; and the area average grain size of a plurality of grains observed on the sputtering surface 10s, preferably on the sputtering surface 10s and in a cross section parallel to the sputtering surface 10s (hereinafter also referred to as "area average grain size Nv") is 3.0 μm or more. Thus, a target material 10 with low density and crack resistance can be obtained.

[0051] By setting the density of the target material 10 to 4.2 g / cm 3 Hereinafter, even if the heating temperature in the oxidation treatment (step E) described later is low, oxygen (O) can be sufficiently introduced into the center of the target 10, and the target 10 can be sufficiently oxidized to the center. Thus, a target 10 can be obtained in which the composition of O is a desired composition in the entire region (the entire region in the thickness direction and the in-plane direction of the target 10).

[0052] In addition, by setting the density of the target material 10 to 4.2 g / cm 3Next, the target material 10 can be manufactured by lowering the heating temperature in the oxidation treatment described later. Therefore, during the oxidation treatment, it is possible to suppress the scattering (volatilization) of K (K component) in a part of the target material 10. Thus, it is possible to obtain a target material 10 in which the composition of K in all regions is a desired composition.

[0053] As described above, by setting the density of the target material 10 to 4.2 g / cm 3 In the following, a target material 10 having a desired composition of O and K in all regions can be obtained. As a result, a KNN film having predetermined physical properties (crystal quality, thickness, composition, etc.) and predetermined characteristics (piezoelectric characteristics, insulation characteristics, etc.) can be reliably obtained by sputtering film formation using the target material 10. That is, a KNN film with high reliability can be obtained.

[0054] In addition, by setting the density of the target material 10 to 4.2 g / cm 3 Then, the target material 10 can be manufactured by lowering the heating temperature in the oxidation treatment described later. Therefore, during the oxidation treatment, the target material 10 is less likely to be warped or cracked, and the production yield of the target material 10 can be improved.

[0055] The density of the target material 10 is preferably 4.0 g / cm 3 Thus, even if the heating temperature in the oxidation treatment is low as described later, oxidation can be reliably performed to the center of the target 10. As a result, the target 10 having the desired composition of O and K in the entire region can be reliably obtained.

[0056] The density of the target material 10 is greater than 4.2 g / cm 3 In the case of the target 10, if the heating temperature in the oxidation treatment is low as described later, the target 10 may not be sufficiently oxidized to the center portion. Therefore, in particular, the composition of O in the center portion of the target 10 may deviate from the desired composition.

[0057] In addition, the density of the target material 10 is greater than 4.2 g / cm 3 In the case of , by setting the heating temperature in the oxidation treatment to a high temperature, the target material 10 is fully oxidized to the center. However, if the heating temperature in the oxidation treatment is set to a high temperature, the target material 10 is fully oxidized to the center, but during the oxidation treatment, the K component of a part of the target material 10 is easily volatilized. Therefore, when the density is greater than 4.2 g / cm 3 In the target material 10, the composition of K may deviate from the desired composition. In addition, if the heating temperature in the oxidation treatment is set to a high temperature, warping and cracking are likely to occur in the target material 10 during the oxidation treatment.

[0058] In addition, the density of the target material 10 is preferably 3.5 g / cm 3Thus, a target material 10 with low density and crack resistance can be obtained reliably. When the density of the target material 10 is less than 3.5 g / cm 3 In the case of , even if the Vickers hardness is 30 to 200 and the area average grain size Nv is 3.0 μm or more, the mechanical strength of the target material 10 may be insufficient. Therefore, a target material 10 with low density and crack resistance may not be obtained.

[0059] The density of the target material 10 can be measured using, for example, the following apparatus and method. An example of a method for measuring the density is given below.

[0060] [Density measurement method]

[0061] Device: ALFA MIRAGE electronic density meter MDS300

[0062] Test method: The density of a target material cut into a predetermined size was measured by the Archimedean method using the above-mentioned apparatus.

[0063] The Vickers hardness of the target material 10 of this embodiment is 30 or more and 200 or less, preferably 30 or more and less than 200, and more preferably 30 or more and less than 150. Thus, a target material 10 having a low density and being resistant to cracking can be obtained.

[0064] When the Vickers hardness of the target material 10 is less than 30, the mechanical strength of the target material 10 may be insufficient even if the area average grain size Nv is 3.0 μm or more. Therefore, a target material 10 having a low density and being resistant to cracking may not be obtained.

[0065] When the Vickers hardness of the target material 10 is greater than 200, a target material 10 with low density and high crack resistance may not be obtained. This is because, in order to obtain a target material 10 with a Vickers hardness greater than 200, the pressure in the hot press sintering (step D) described later (the pressure during sintering described later) needs to be greater than 500 kgf / cm 2 As a result, the density of the target material 10 is greater than 4.2 g / cm 3 In addition, if a target material 10 having a Vickers hardness greater than 200 is to be obtained, it is also possible to consider making the temperature in the hot pressing sintering described later (the sintering temperature described later) greater than 1150° C. In this case, during the implementation of the hot pressing sintering, the K component is easy to volatilize, so there is a case where the K composition deviates from the desired composition.

[0066] The Vickers hardness (Hv) of the target material 10 can be measured using a Vickers hardness tester in accordance with JIS R 1610: 2003. An example of a method for measuring the Vickers hardness and measurement conditions is shown below.

[0067] [Vickers hardness measurement method and measurement conditions]

[0068] Equipment: Micro Vickers hardness tester HM-114 manufactured by Mitutoyo Corporation

[0069] Atmosphere: Atmospheric

[0070] Temperature: Room temperature (25°C)

[0071] Test force: 1.0kgf

[0072] Load application speed: 10μm / s

[0073] Hold time: 15 seconds

[0074] Measurement points: 5 points

[0075] Test method: This test is based on JIS R 1610. A Vickers indenter (a quadrangular pyramid indenter with a square bottom and two facing surfaces at an angle of 136 degrees) is used to calculate the Vickers hardness based on the test force when a pit is formed on the test surface and the pit surface area calculated from the diagonal length of the pit. The average of the measurement results at 5 points is calculated.

[0076] In addition, the target material 10 of this embodiment has an area average grain size Nv of 3.0 μm or more. By setting the Vickers hardness of the target material 10 to a predetermined range and forming the target material 10 with grains having a large average grain size, the mechanical strength of the target material 10 can be improved. As a result, a target material 10 that is resistant to cracking even at a low density can be obtained.

[0077] The area average grain size Nv of the target material 10 is preferably 5.0 μm or more. This can reliably improve the mechanical strength of the target material 10 .

[0078] When the target material 10 has an area average grain size Nv of less than 3.0 μm, the target material 10 cannot have a low density and a sufficiently high mechanical strength, and cracks and notches are likely to occur in the target material 10 during production of the target material 10 or during sputtering film formation. In other words, a target material 10 with a low density and resistance to cracking may not be obtained.

[0079] The area average grain size Nv (μm) can be obtained by analyzing the backscattered electron diffraction pattern (EBSD) image of the sputtering surface 10s of the target 10 or the cross section parallel to the sputtering surface 10s. The grain diameter obtained by the EBSD-based analysis is expressed as the diameter of a circle with the same area as the measured grain. The area average grain size Nv (μm) can be the average grain size obtained by the Area Fraction method. In the Area Fraction method, the proportion of the area of ​​each grain in the total area is multiplied by each area value, and the total value of the obtained values ​​becomes the average area of ​​the grain. The diameter when the calculated area is assumed to be a circle becomes the average grain size. It should be noted that in the EBSD analysis, the boundary where the crystal orientation difference is greater than a certain value, such as 15° or more, is regarded as a grain boundary, and the area average grain size Nv (μm) can be obtained.

[0080] Alternatively, the area average particle size Nv (μm) may be a value calculated using the following formula. In the following formula, d i represents the grain size of the observed grain (μm), n i Represents the observed particle size d i The number of grains (μm). i It is the diameter of a perfect circle having an area equal to the area of ​​the observed crystal grain, that is, the equivalent circle diameter (μm).

[0081] Area average particle size Nv (μm) = Σ (d i 3 ×n i ) / Σ(d i 2 ×n i )

[0082] The area average particle size Nv (μm) is an average value obtained by weighting according to the size of the particle area.

[0083] As will be described in detail later, the target material 10 of this embodiment is produced by subjecting a sintered powder (KNN sintered powder) containing K, Na, Nb, and O to hot pressing and sintering under predetermined conditions. In addition, when the KNN sintered powder is produced, a raw material powder containing Na and a raw material powder containing Nb are mixed and sintered to produce a sintered powder containing Na and Nb (NaNbO 3 In addition, a raw material powder containing K and a raw material powder containing Nb are mixed and sintered to produce a sintered powder containing K and Nb (KNbO 3 powder), thereafter, the prepared NaNbO 3 Powder and KNbO 3The powders are mixed and calcined to produce KNN sintered powder. 3 Powder and KNbO 3 When powdered, NaNbO 3 The sintering temperature of the powder is higher than that of KNbO 3 The sintering temperature during the production of powders was used to produce NaNbO 3 Powder and KNbO 3 pink.

[0084] The target material 10 of this embodiment is produced by hot pressing and sintering the KNN sintered powder produced by the above method. Therefore, the target material 10 of this embodiment can have the following three characteristics: density of 4.2 g / cm 3 The following characteristics: a characteristic that the Vickers hardness is 30 or more and 200 or less; and a characteristic that the area average grain size Nv is 3.0 μm or more.

[0085] In addition, since the target material 10 is made by using the KNN sintered powder produced by the above method, the target material 10 of the present embodiment can further have the following characteristics, that is, the plurality of crystal grains observed on the sputtering surface 10s, preferably on the sputtering surface 10s and the cross section parallel to the sputtering surface 10s mainly include: a plurality of crystal grains containing oxides containing Na and Nb (NaNbO 3 grains); and a plurality of grains containing oxides containing K and Nb (KNbO 3 The NaNbO 3 Grain confirmation: Na and Nb were detected in the KNbO 3 In the part where K and Nb were detected, it was confirmed that the plurality of crystal grains observed in the sputtering surface 10s mainly consisted of NaNbO 3 Grains and KNbO 3 Grain.

[0086] In addition, since the target 10 is made using the KNN sintered powder produced by the above-mentioned new method, the target 10 of this embodiment can further have the following characteristics, that is, a portion with a high content of Na (hereinafter referred to as a Na-rich portion) and a portion with a high content of K (hereinafter referred to as a K-rich portion) are respectively dispersed on the sputtering surface 10s, preferably on the sputtering surface 10s and the cross section parallel to the sputtering surface 10s. The so-called Na-rich portion is a portion of the target 10 with a higher Na concentration than the average Na concentration, and the so-called K-rich portion is a portion of the target 10 with a higher K concentration than the average K concentration. In addition, if the sputtering surface 10s and the cross section parallel to the sputtering surface 10s are observed using Energy Dispersive X-ray Spectroscopy (EDX) or SEM-EDX, it can be confirmed that the Na-rich portion and the K-rich portion are dispersed on the sputtering surface 10s, preferably on the sputtering surface 10s and the cross section parallel to the sputtering surface 10s.

[0087] (2) Target material manufacturing method

[0088] In reference Figure 2 At the same time, a suitable embodiment of the method for producing the target material 10 of this embodiment will be described in detail.

[0089] In the production process of the target material 10 of this embodiment, the following steps are performed:

[0090] A step of mixing a raw material powder containing a compound including Na and a raw material powder containing a compound including Nb at a predetermined ratio, and heating the mixed powder in an oxygen-containing atmosphere to produce a calcined powder containing Na and Nb (step A);

[0091] A step of mixing a raw material powder containing a compound including K and a raw material powder containing a compound including Nb at a predetermined ratio, and heating the mixed powder in an oxygen-containing atmosphere to produce a calcined powder containing K and Nb (step B);

[0092] a step of mixing the calcined powder produced in step A and the calcined powder produced in step B at a predetermined ratio, and heating (calcining) the mixed powder in an oxygen-containing atmosphere to produce a calcined powder containing K, Na and Nb (step C); and

[0093] A step of applying a predetermined pressure to the calcined powder produced in step C to produce a green compact, and (simultaneously) heating the green compact to produce a sintered body (step D).

[0094] In addition, in the production process of the target material 10 of the present embodiment, the heating temperature in step A is set higher than the heating temperature in step B.

[0095] In addition, in step C, the sintered powder prepared in step A, the sintered powder prepared in step B, and a powder containing at least one element selected from Cu and Mn can be mixed in a specified ratio to prepare a sintered powder that contains K, Na and Nb and also contains at least one element selected from Cu and Mn as a dopant.

[0096] In addition, after step D, the sintered body is further heat-treated at a heating temperature of 500° C. to 1100° C. for 1 hour or more in an oxygen-containing atmosphere (step E).

[0097] <Step A: Preparation of sintered powder containing Na and Nb>

[0098] In this step, a raw material powder containing a compound including Na and a raw material powder containing a compound including Nb are mixed at a predetermined ratio, and the obtained mixed powder is heated in an oxygen-containing atmosphere to produce (synthesize) a calcined powder containing Na and Nb.

[0099] (Preparation of starting material powder)

[0100] First, as starting raw material powders in this step, powders containing a compound containing Na and powders containing a compound containing Nb are prepared. For example, sodium carbonate (Na 2 CO 3 ) powder, niobium pentoxide (Nb 2 O 5 )pink.

[0101] The "powder containing a compound containing Na" mentioned here means a powder having a compound containing Na as a main component. In addition to the case where the powder is composed of a powder containing a compound containing Na only, there is also a case where the powder contains powders of other compounds on the basis of the powder containing a compound containing Na as a main component. Similarly, the "powder containing a compound containing Nb" means a powder having a compound containing Nb as a main component. In addition to the case where the powder is composed of a powder containing a compound containing Nb only, there is also a case where the powder contains powders of other compounds on the basis of the powder containing a compound containing Nb as a main component. The so-called Na compound is at least one selected from the group consisting of Na oxides, Na composite oxides, and Na compounds that become oxides by heating, for example, the carbonates shown above, and oxalates, etc. can also be mentioned. The so-called Nb compound is at least one selected from the group consisting of Nb oxides, Nb composite oxides, and Nb compounds that become oxides by heating, for example, the niobium pentoxide shown above, etc. can be mentioned.

[0102] The average diameter of the secondary particles of these starting material powders is preferably, for example, less than 1 mm, and the starting material powders are preferably subjected to coarse pulverization or the like before weighing, as necessary.

[0103] (weighing, mixing)

[0104] Next, weigh the Na and 2 CO 3 Powder and Nb 2 O 5 The Na content is adjusted so that the obtained calcined powder containing Na and Nb has a desired composition. 2 CO 3 Powder and Nb 2 O 5 The weighing can be performed in the air, but is preferably performed in an atmosphere with low humidity such as an inert gas atmosphere, a vacuum, or a dry air atmosphere. In addition, it is preferably performed in an atmosphere with Na 2 CO 3 Powder and Nb 2 O 5 After the powder is fully dried, 2 CO 3 Powder and Nb 2 O 5 Powder using Henschel mixer, blender, ribbon mixer, high-speed mixer (super mixer)

[0105] The ingredients may be mixed in a dry or wet manner using mixers such as a Nauta mixer, an intensive mixer, a ball mill, or an automatic mortar.

[0106] (One-time firing)

[0107] The obtained Na 2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder is fired once in an atmosphere containing oxygen (O) such as air or oxygen gas (oxidizing atmosphere) using an electric furnace, etc., to obtain a fired powder containing Na and Nb (NaNbO 3 Powder). It is preferred to use Na 2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder undergoes a solid phase reaction, thereby obtaining NaNbO in which Na and Nb are in a solid solution state. 3 pink.

[0108] The present inventors have found that by increasing the Na 2 CO 3 Powder and Nb 2 O 5The heating temperature during the primary firing of the mixed powder of the powder (hereinafter also referred to as "primary firing temperature A") can increase the NaNbO 3 The average diameter of the primary particles of the powder (average primary particle size). It should be noted that even if the primary sintering temperature A is increased, the NaNbO 3 In the production of powder, Na and Nb are basically not volatilized. 3 The average primary particle size of the powder is such that the target material 10 having an area average particle size Nv of 3.0 μm or more can be easily obtained. 3 The average primary particle size of the powder is calculated from the images of the NaNbO powder observed at a magnification of 2000 to 5000 times using a scanning electron microscope (SEM). 3 The median diameter D of the primary particles of the powder 50 In addition, the term "primary particle" in this specification refers to a single particle.

[0109] The primary calcination temperature A is a temperature higher than the primary calcination temperature B in the step B described later. The primary calcination temperature A is preferably set to a temperature that allows NaNbO 3 The average primary particle size of the powder is larger than that of the KNbO prepared in step B. 3 The average primary particle size of the powder is the temperature. 3 The average primary particle size of the powder can be increased by increasing the primary sintering temperature A, and thus is likely to be larger than that of KNbO 3 In this step, by making NaNbO 3 The average primary particle size of the KNN calcined powder obtained in the later-described step C is also likely to increase. Therefore, the average diameter of the crystal grains constituting the target material 10 finally obtained is also likely to increase. As a result, it is easier to obtain the target material 10 having the characteristic of having an area average particle size Nv of 3.0 μm or more.

[0110] The primary sintering temperature A is preferably such that NaNbO 3 The average primary particle size of the powder is larger than that of KNbO 3 In addition, the primary sintering temperature A is preferably such that the NaNbO 3 The average primary particle size of the powder is, for example, 5.0 μm or more. By producing KNbO 3 The average primary particle size of the powder is the average primary particle size of NaNbO 3 Powder, for example, to produce NaNbO with an average primary particle size of 5.0 μm or more 3 The target material 10 having the characteristic of having an area average grain size Nv of 3.0 μm or more can be obtained reliably.

[0111] The primary sintering temperature A is preferably 1000° C. or higher. This can produce NaNbO having a large average primary particle size. 3 powder, such as NaNbO having an average primary particle size of 5.0 μm or more 3 Powder. Reliably obtain NaNbO with a large average primary particle size 3 From the viewpoint of the powder, the primary sintering temperature A is more preferably 1100° C. or higher. It should be noted that when the primary sintering temperature A is less than 1000° C., the NaNbO 3 The average primary particle size of the powder may not be sufficiently increased. 3 The situation of primary particles of powder.

[0112] The upper limit of the primary calcination temperature A is not particularly limited, but is preferably 1300° C. or lower, for example. When the primary calcination temperature A is higher than 1300° C., the NaNbO 3 The effect of the average primary particle size of the powder reaches its limit. On the other hand, there is NaNbO 3 The manufacturing cost of the powder increases. Regarding the primary firing temperature A, it is necessary to reliably avoid NaNbO 3 From the viewpoint of increasing the production cost of the powder, the temperature is preferably 1250° C. or lower, and more preferably 1200° C. or lower.

[0113] The time for performing the primary calcination in this step is not particularly limited, but is preferably 3 hours to 20 hours, more preferably 4 hours to 15 hours, and even more preferably 5 hours to 10 hours.

[0114] (Coarse crushing)

[0115] Thereafter, the obtained NaNbO may be pulverized using a pulverizing mechanism such as a ball mill, a bead mill, a vibration mill, an attritor, a jet mill, an atomizer, or a cutter mill as required. 3 The secondary particles of the powder are coarsely crushed. It should be noted that the so-called secondary particles are aggregates obtained by agglomeration of primary particles. In addition, the purpose of the coarse crushing here is to break up the NaNbO 3 Secondary particles of powder, coarsely crushed in NaNbO 3 The process is carried out under the condition that the average primary particle size of the powder does not decrease (does not change).

[0116] It should be noted that the above-mentioned primary calcination and coarse pulverization processes may be repeated partially or entirely as required, and coarse pulverization may be omitted. In addition, screening processes may be added after these processes are completed or in the intervals between the processes. The mixing and pulverization mechanisms are not limited to the above-mentioned examples, and may be widely adopted from other pulverization mechanisms. In addition, the conditions at this time may also be widely selected according to the purpose of obtaining the above-mentioned specifications.

[0117] <Step B: Preparation of sintered powder containing K and Nb>

[0118] In this step, a raw material powder containing a compound including K and a raw material powder containing a compound including Nb are mixed at a predetermined ratio, and the obtained mixed powder is heated in an atmosphere containing O to produce (synthesize) a sintered powder containing K and Nb.

[0119] (Preparation of starting material powder)

[0120] First, as starting raw material powders in this step, powders containing a compound containing K and powders containing a compound containing Nb are prepared. For example, potassium carbonate (K 2 CO 3 ) powder, Nb 2 O 5 pink.

[0121] It should be noted that the "powder containing a compound containing K" in this specification means a powder containing a compound containing K as a main component, and includes a case where the powder is composed of only a powder containing a compound containing K as a main component, and also includes a case where the powder contains other compounds in addition to the powder containing a compound containing K as a main component. The so-called K compound is at least one selected from K oxides, K composite oxides, and K compounds that become oxides by heating, and for example, in addition to the carbonates shown above, oxalates and the like can also be mentioned.

[0122] The average diameter of the secondary particles of these starting material powders is preferably, for example, less than 1 mm, and the starting material powders are preferably subjected to coarse pulverization or the like before weighing, as necessary.

[0123] (weighing, mixing)

[0124] Next, weigh the K 2 CO 3 Powder and Nb 2 O 5 The K content is adjusted so that the obtained sintered powder containing K and Nb has a desired composition. 2 CO 3 Powder and Nb 2 O 5The weighing can be performed in the air, but is preferably performed in an atmosphere with low humidity such as an inert gas atmosphere, a vacuum atmosphere, or a dry air atmosphere. In addition, it is preferred to make K 2 CO 3 Powder and Nb 2 O 5 After the powder is fully dried.

[0125] The present inventors have found that by adjusting K 2 CO 3 Powder and Nb 2 O 5 The mixing ratio of the powder can be adjusted to adjust the sintered powder (KNbO 3 This is a new insight first discovered by the inventors. By making KNbO with a large average primary particle size in this step, 3 The KNN sintered powder can reliably increase the average primary particle size of the KNN sintered powder obtained in step C described later. Therefore, the average particle size of the grains constituting the target material 10 obtained in the end can be reliably increased. As a result, the target material 10 having the characteristic of having an area average particle size Nv of 3.0 μm or more can be reliably obtained. It should be noted that the so-called "KNbO 3 The average primary particle size of the powder is the KNbO calculated from the SEM images observed at a magnification of 2000 to 5000 times. 3 The median diameter D of the primary particles of the powder 50 .

[0126] It is preferred to make KNbO 3 The K is adjusted so that the average primary particle size of the powder is, for example, 3.0 μm or more. 2 CO 3 Powder and Nb 2 O 5 In this step, KNbO having an average primary particle size of, for example, 3.0 μm or more, more preferably 5.0 μm or more is prepared. 3 The target material 10 having the characteristic of having an area average grain size Nv of 3.0 μm or more can be obtained more reliably.

[0127] It is preferred to make KNbO 3 The composition of the powder is adjusted to be rich in K. 2 CO 3 Powder and Nb 2 O 5 Thus, KNbO with a large average primary particle size can be reliably obtained. 3 Powder, for example, KNbO having an average primary particle size of 3.0 μm or more 3Powder. By making the KNbO 3 The composition of the powder is adjusted to be rich in K. 2 CO 3 Powder and Nb 2 O 5 The mixing ratio of KNbO 3 The average primary particle size of the powder is a new finding discovered by the inventors for the first time. The "K-rich composition" mentioned here means that the composition is rich in KNbO. 3 The ratio of K composition to the total composition of the powder (=K composition / KNbO 3 The total composition of the powder) is higher than that of KNbO 3 The ratio of Nb composition to the total composition of the powder (=Nb composition / KNbO 3 powder).

[0128] It is preferred that the KNbO 3 The K content is adjusted so that the ratio of the K composition to the Nb composition in the powder (hereinafter referred to as the K / Nb ratio) is, for example, 1.005 or more, preferably 1.010 or more, and more preferably 1.015 or more. 2 CO 3 Powder and Nb 2 O 5 Thus, KNbO with a large average primary particle size can be obtained more reliably. 3 Powder, for example, KNbO having an average primary particle size of 3.0 μm or more 3 In addition, it is preferred to adjust K so that the K / Nb ratio is 1.1 or less, more preferably 1.08 or less. 2 CO 3 Powder and Nb 2 O 5 Thus, it is possible to avoid 3 Crystals with crystal structures other than perovskite are mixed into the powder. 3 If crystals having a crystal structure other than the perovskite structure exist in the powder, the crystals may adversely affect the sintering reaction and the growth of crystal grains in the hot press sintering (step D) described later.

[0129] Next, the weighed K 2 CO 3 Powder and Nb 2 O 5 Mixing of Powders Powders are mixed by dry or wet methods using a mixer such as a Henschel mixer, a stirrer, a ribbon mixer, a high-speed mixer, a Nauta mixer, a intensive mixer, a ball mill, or an automatic mortar.

[0130] (One-time firing)

[0131] The obtained K 2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder is fired once in an atmosphere containing O using an electric furnace or the like to obtain a fired powder containing K and Nb (KNbO 3 Powder). It is preferred to use K in one sintering. 2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder undergoes a solid phase reaction, thereby obtaining KNbO in which K and Nb are in a solid solution state. 3 pink.

[0132] Carry out K 2 CO 3 Powder and Nb 2 O 5 The heating temperature during the primary firing of the powder mixture (hereinafter also referred to as “primary firing temperature B”) is a temperature lower than the primary firing temperature A described above.

[0133] Regarding the primary firing temperature B, the desired composition of KNbO is obtained. 3 From the viewpoint of powder, it is preferably less than 1000°C, more preferably 900°C or less, and even more preferably 800°C or less. When the primary calcination temperature B is 1000°C or more, in the primary calcination, KNbO 3 A portion of K in the powder is easily volatilized. 3 The K composition in the powder may deviate from the desired composition. As a result, the K composition in the target material 10 finally obtained may deviate from the desired composition.

[0134] In addition, regarding the primary sintering temperature B, it is possible to reliably obtain KNbO with a large average primary particle size. 3 Powder, for example, KNbO having an average primary particle size of 3.0 μm or more 3 From the perspective of powder, it is preferably 500°C or higher, more preferably 600°C or higher, further preferably 650°C or higher, and particularly preferably 700°C or higher. When the primary calcination temperature B is less than 500°C, even if K is adjusted 2 CO 3 Powder and Nb 2 O 5 The mixing ratio of the powder may not be able to fully increase the KNbO 3 The average primary particle size of the powder, i.e., the KNbO 3 The situation of primary particles of powder.

[0135] The time for performing the primary calcination in this step is not particularly limited, but is preferably 3 hours to 20 hours, more preferably 4 hours to 15 hours, and even more preferably 5 hours to 10 hours.

[0136] (Coarse crushing)

[0137] Thereafter, the obtained KNbO can be pulverized using a pulverizing mechanism such as a ball mill, a bead mill, a vibration mill, an attritor, a jet mill, an atomizer, a cutter, or the like as required. 3 The secondary particles of the powder are coarsely crushed. It should be noted that the purpose of the coarse crushing here is to break up the KNbO 3 Secondary particles of powder, coarsely crushed in KNbO 3 This is carried out under the condition that the average primary particle size of the powder does not decrease.

[0138] It should be noted that the above-mentioned primary calcination and coarse pulverization processes may be repeated partially or entirely as required, and coarse pulverization may be omitted. In addition, screening processes may be added after these processes are completed or in the intervals between the processes. The mixing and pulverization mechanisms are not limited to the above-mentioned examples, and may be widely adopted from other pulverization mechanisms. In addition, the conditions at this time may also be widely selected according to the purpose of obtaining the above-mentioned specifications.

[0139] <Step C: Preparation of sintered powder containing K, Na and Nb>

[0140] Next, the NaNbO prepared in step A 3 Powder and KNbO prepared in step B 3 The powders are mixed at a predetermined ratio, and the obtained mixed powder is heated (calcined) in an atmosphere containing O to produce a calcined powder containing K, Na, Nb, and O (KNN calcined powder).

[0141] (Preparation of starting material powder)

[0142] First, as the starting raw material powder in this step, the NaNbO prepared in step A is prepared. 3 powder and KNbO prepared in step B 3 In addition, as required, as the starting raw material powder in this step, a powder containing at least one dopant element selected from Cu and Mn, for example, a powder of a single substance of the element, an oxide powder containing the element, a composite oxide powder containing the element, and a powder of a compound containing the element that becomes an oxide by heating (for example, a carbonate, an oxalate) is prepared.

[0143] The average diameter of the secondary particles of these starting material powders is preferably, for example, less than 1 mm, and the starting material powders are preferably subjected to coarse pulverization or the like before weighing, as necessary.

[0144] (weighing, mixing)

[0145] Next, weigh NaNbO 3 Powder and KNbO 3 The NaNbO powder is adjusted so that the composition of the target material 10 finally obtained becomes the desired composition. 3 Powder and KNbO 3 The weighing can be performed in the air, but is preferably performed in an atmosphere with low humidity such as an inert gas atmosphere, a vacuum atmosphere, or a dry air atmosphere. In addition, it is preferred to make NaNbO 3 Powder and KNbO 3 Next, weigh the NaNbO 3 Powder and KNbO 3 The mixed powder is mixed in a dry or wet manner using a mixer such as a Henschel mixer, a stirrer, a ribbon mixer, a high-speed mixer, a Nauta mixer, a powerful mixer, or an automatic mortar. It should be noted that in this step, as the starting raw material powder, NaNbO having a large average primary particle size is used. 3 KNbO powder and large average primary particle size 3 Therefore, even if the mixing process is fully performed, the average primary particle size of the KNN mixed powder can be maintained at, for example, 3.0 μm or more. It should be noted that the so-called "average primary particle size of the KNN mixed powder" in this specification is the median diameter D of the primary particles of the KNN mixed powder read and calculated from the SEM image observed at a magnification of 2000 to 5000 times. 50 .

[0146] (Coarse crushing)

[0147] Thereafter, NaNbO 3 Powder and KNbO 3 The mixed powder of the powder is coarsely pulverized using a pulverizing mechanism such as a ball mill, a bead mill, a vibration mill, an attritor, a jet mill, an atomizer, a shredder, etc. to obtain a mixed powder containing K, Na and Nb (hereinafter referred to as KNN mixed powder). The purpose of the coarse pulverization is to break up NaNbO 3 Powder and KNbO 3 The secondary particles of the powder are prepared under the condition that the average primary particle size of the KNN mixed powder after the coarse pulverization does not decrease.

[0148] (Calcination, coarse grinding)

[0149] The obtained KNN mixed powder is calcined in an oxygen-containing atmosphere using an electric furnace or the like. By performing this calcination, impurities such as moisture, carbon components, and chlorine can be removed from the KNN mixed powder, and a high-purity KNN calcined powder ((K, Na)NbO3 Powder, hereinafter referred to as KNN fired powder).

[0150] The heating temperature during calcination (hereinafter referred to as calcination temperature) is preferably 500° C. or higher, more preferably 600° C. or higher, further preferably 650° C. or higher, and particularly preferably 700° C. or higher, from the viewpoint of obtaining a KNN calcined powder with high purity. In addition, the calcination temperature is preferably 1100° C. or lower, more preferably 1000° C. or lower, further preferably 900° C. or lower, and particularly preferably 800° C. or lower, from the viewpoint of suppressing the volatilization of K in the KNN mixed powder and obtaining a KNN calcined powder of a desired composition.

[0151] The heating time during calcination is not particularly limited, but is preferably 1 hour to 50 hours, more preferably 3.5 hours to 40 hours, further preferably 4 hours to 30 hours, and particularly preferably 5 hours to 12 hours.

[0152] In the calcination step, from the viewpoint of facilitating the removal of impurities, a multi-stage heat treatment may be performed at different calcination temperatures.

[0153] After calcination, the powder is coarsely pulverized as required by a pulverizing mechanism such as a ball mill, a bead mill, a vibration mill, an attritor, a jet mill, an atomizer, etc. The coarse pulverization is performed under conditions such that the secondary particles of the KNN calcined powder after the coarse pulverization become small.

[0154] (fine grinding)

[0155] The KNN sintered powder obtained by coarse pulverization can be further pulverized using a pulverizing mechanism such as a ball mill, a bead mill, a vibration mill, a grinder, an atomizer, and a jet mill, preferably a jet mill. The fine pulverization is performed under the condition that the average primary particle size of the KNN sintered powder after fine pulverization is maintained at, for example, 3.0 μm or more. It should be noted that the so-called "average primary particle size of the KNN sintered powder" in this specification is the median diameter D of the primary particles of the KNN sintered powder read and calculated from the SEM image observed at a magnification of 2000 to 5000 times. 50 .

[0156] By the above treatment, the KNN sintered powder used in the hot press sintering of this method can be obtained. As mentioned above, in this step, due to the use of NaNbO with a large average primary particle size, 3 KNbO powder and large average primary particle size 3Since the powder is used as the starting raw material powder, even if the above-mentioned mixing, coarse pulverization, and fine pulverization are performed, a KNN calcined powder with a large average primary particle size, for example, a KNN calcined powder with an average primary particle size of 3.0 μm or more can be obtained. In addition, the obtained KNN calcined powder can be further heated and dried at 180 to 200° C. as needed.

[0157] It should be noted that the above-mentioned calcination, coarse pulverization, fine pulverization and the like can be repeatedly implemented in part or in whole as required, and any of the above-mentioned treatments can be omitted. In addition, screening treatments can be added after these treatments are completed or in the gaps between the treatments. The mixing and pulverization mechanisms are not limited to the above-mentioned examples, and can be widely adopted from other pulverization mechanisms. In addition, the conditions at this time can also be widely selected according to the purpose of obtaining the above-mentioned specifications.

[0158] <Step D: Hot Press Sintering>

[0159] In this step, mechanical pressure is applied to the KNN sintered powder obtained by implementing the above steps A to C to form a powder compact, and the powder compact is simultaneously heated to sinter the KNN sintered powder, i.e., so-called hot pressing is performed to produce a KNN sintered body. Figure 2 At the same time, a suitable method of hot pressing sintering is described.

[0160] Figure 2 2 is a schematic diagram of the structure of a sintering device 200 used in hot press sintering. Figure 2 The sintering device 200 shown has a processing container 203 made of SUS or the like, and has a processing chamber 201 therein. In the processing chamber 201, there is provided a pressing mechanism 217 (for example, a hydraulic type pressing mechanism 217) configured to apply a predetermined pressure to the KNN sintered powder 210 filled in the fixture (sintering mold) 208. In addition, in the processing chamber 201, there is provided a heater 207 for heating the KNN sintered powder 210 in the fixture 208 to a predetermined temperature. The heater 207 is arranged in a concentric circle surrounding the fixture 208. In the processing chamber 201, there is provided a temperature sensor 209 for measuring the temperature in the processing chamber 201. Each component of the sintering device 200 is connected to a controller 280 configured as a computer, and is configured to control the steps and conditions described later by a program executed on the controller 280.

[0161] First, the KNN sintered powder 210 prepared in step C is filled into the fixture 208. At this time, the KNN sintered powder 210 is filled into the fixture 208 in a manner that minimizes uneven filling of the KNN sintered powder 210. The fixture 208 is preferably made of a material such as graphite. In addition, the fixture 208 is configured to be able to be put into the processing chamber 201 of the sintering device 200 and not be damaged by the pressurization of the pressing mechanism 217.

[0162] Then, the fixture 208 filled with the KNN sintered powder 210 is placed in the processing chamber 201 and arranged at a predetermined position of the pressing mechanism 217. Thereafter, the processing chamber 201 is made to be a nitrogen atmosphere, an inert gas atmosphere (e.g., an atmosphere containing an inert gas such as argon or helium), or a vacuum atmosphere. When the processing chamber 201 is made to be in a predetermined atmosphere, the pressing mechanism 217 is operated to start pressurizing the KNN sintered powder 210 filled in the fixture 208, and at the same time, the KNN sintered powder 210 is heated by the heater 207. Figure 2 As shown by the hollow arrow in the figure, the pressing mechanism 217 is configured to apply pressure to the pressing surface in the vertical direction. As the pressing mechanism 217 starts to work, the mechanical pressure applied to the KNN sintered powder 210 gradually increases to a predetermined sintering pressure described later, and as the KNN sintered powder 210 starts to be heated by the heater 207, the temperature of the pressed powder body formed by pressurizing the KNN sintered powder 210 gradually increases from the initial temperature of about room temperature (25°C) to a predetermined sintering temperature described later.

[0163] When the pressure applied to the KNN sintered powder 210 reaches a predetermined sintering pressure, and the temperature of the KNN sintered powder 210 (powder compact) reaches a predetermined sintering temperature, the state of reaching the predetermined sintering pressure and the predetermined sintering temperature is maintained for a predetermined time. Thus, the sintering reaction of the KNN sintered powder 210 in the powder compact is advanced, and a KNN sintered body is obtained.

[0164] As the conditions for hot press sintering, the following conditions can be exemplified.

[0165] [Hot Press Sintering Conditions]

[0166] Atmosphere: Nitrogen atmosphere, inert gas atmosphere or vacuum atmosphere

[0167] Sintering pressure (load): 100kgf / cm 2 Above and 500kgf / cm 2 Below, preferably 300kgf / cm 2 Above and 400kgf / cm 2 the following

[0168] Sintering temperature: 800°C to 1150°C, preferably 850°C to 1000°C, more preferably 900°C to 970°C

[0169] Sintering time: 1 hour or more and 5 hours or less, preferably 2 hours or more and 3 hours or less

[0170] By hot pressing and sintering the KNN sintered powder 210 obtained by implementing the above steps A to C under the above conditions, a KNN sintered body having the following three characteristics can be obtained, and then a target material 10 can be obtained. The three characteristics are: a density of 4.2 g / cm 3 The target material 10 having the following three characteristics is easily obtained by setting the sintering pressure and the sintering temperature within the above ranges.

[0171] It should be noted that it is known from experience that the particle size of the KNN sintered powder 210 after hot pressing sintering changes relative to the particle size of the KNN sintered powder 210 before hot pressing sintering, especially KNbO 3 The particle size of the powder tends to change easily. In addition, the area average particle size Nv of the target material 10 after hot pressing and sintering obtained by EBSD tends to become a value smaller than the average primary particle size of the KNN sintered powder 210 before hot pressing and sintering obtained from the SEM image. Therefore, although it is difficult to compare the changes in the particle size of the KNN sintered powder 210 before and after sintering with different measurement methods, in order to make the area average particle size Nv of the target material 10 after hot pressing and sintering obtained by EBSD to be 3.0μm or more, it is important to increase the average primary particle size of the KNN sintered powder 210 obtained by implementing the above-mentioned steps A to C, especially the NaNbO 3 The average primary particle size of the powder was determined by changing the NaNbO 3 The average primary particle size of the powder is 5.0 μm or more, KNbO 3 The average primary particle size of the powder is 3.0 μm or more, and thus the target material 10 having the characteristic that the area average particle size Nv obtained by EBSD is 3.0 μm or more can be obtained reliably.

[0172] The pressure during sintering is less than 100kgf / cm 2 When the sintering temperature is less than 800°C, the Vickers hardness of the target material 10 may be less than 30. In addition, when the sintering pressure is greater than 500 kgf / cm 2 In the case of the powder compact being overly densified, the density of the target material 10 is greater than 4.2 g / cm 3In addition, when the sintering temperature is higher than 1150° C., a portion of K in the KNN sintered powder is likely to volatilize, and the target material 10 of a desired composition may not be obtained.

[0173] In addition, by setting the sintering pressure to 300 kgf / cm 2 Above and 400kgf / cm 2 By setting the sintering temperature to 850°C or higher, preferably 900°C or higher, the target material 10 having the above three characteristics can be reliably obtained. In addition, by setting the sintering temperature to 1000°C or lower, preferably 970°C or lower, the volatilization of K in a part of the KNN sintered powder can be reliably avoided, and the target material 10 of the desired composition can be reliably obtained.

[0174] <Step E: Oxidation treatment>

[0175] Since the above-mentioned step D (hot pressing sintering) is performed in a nitrogen atmosphere, an inert gas atmosphere, or a vacuum atmosphere, when step D is performed, a part of oxygen (O) of the KNN sintered powder is separated. Therefore, there is a case where the composition of the target material 10 finally obtained becomes a composition deviating from the desired composition, specifically, a composition where the composition of O deviates from the desired composition. Therefore, after performing step D, the target material 10 (oxide sintered body) is subjected to heat treatment (oxidation treatment) in an atmosphere containing O. Thus, O can be introduced into the target material 10 from which a part of O has been separated due to the implementation of step D, so that the composition of the target material 10 finally obtained becomes the desired composition.

[0176] This step is performed in an atmosphere containing oxygen, for example, at a heating temperature of 500° C. to 1100° C., preferably 600° C. to 950° C., more preferably 650° C. to 900° C. The heating time in this step can be, for example, 1 hour or more, preferably 5 hours or more, more preferably 10 hours or more.

[0177] By performing oxidation treatment on the target 10 prepared in the above step D under the above conditions, O can be sufficiently introduced into the center of the target 10 and sufficiently oxidized to the center of the target 10. As a result, the composition of the target 10 finally obtained can be made a desired composition.

[0178] It should be noted that the target material 10 obtained in step D is a low-density target material 10, specifically, a target material with a density of 4.2 g / cm 3Therefore, even if the heating temperature in the oxidation treatment is 1100°C or less, preferably 950°C or less, and particularly preferably 900°C or less, that is, even if the heating temperature in the oxidation treatment is low, O can be sufficiently introduced into the center of the target 10 and sufficiently oxidized to the center of the target 10. Thus, the composition of O can be made a desired composition in the entire region of the target 10 (in the entire region in the thickness direction and in-plane direction of the target 10).

[0179] Furthermore, by lowering the heating temperature during the oxidation treatment, it is possible to suppress the volatilization of K in a part of the target 10 during the oxidation treatment. Thus, the composition of K in the entire region of the target 10 can be made a desired composition.

[0180] Furthermore, by setting the heating temperature in the oxidation treatment to a low temperature, warping and cracking are less likely to occur in the target material 10 during the oxidation treatment. As a result, the production yield of the target material 10 can be improved.

[0181] In addition, since the target material 10 has a low density, by setting the heating time at the above heating temperature to be 1 hour or more, O can be sufficiently introduced into the center of the target material 10 and sufficiently oxidized to the center of the target material 10. In addition, by setting the heating time at the above heating temperature to be 5 hours or more, the target material 10 can be reliably oxidized to the center of the target material 10, and by setting the heating time at the above heating temperature to be 10 hours or more, the target material 10 can be sufficiently and reliably oxidized to the center of the target material 10.

[0182] When the heating temperature in the oxidation treatment is less than 500°C and the heating time at the above heating temperature is less than 1 hour, it is difficult to fully oxidize even the low-density target 10 to the center of the target 10. Therefore, it may be impossible to make the composition of O to be the desired composition in the entire region of the target 10. In addition, when the heating temperature in the oxidation treatment is higher than 1100°C, K in a part of the target 10 volatilizes, and it may be impossible to make the composition of K to be the desired composition in the entire region of the target 10. In addition, during the implementation of the oxidation treatment, warping and cracking are likely to occur in the target 10.

[0183] It should be noted that the upper limit of the heating time at the above heating temperature is not particularly limited. However, if the heating time is too long, the effect of introducing O into the target material 10 reaches a limit, and on the other hand, a part of K in the target material 10 may volatilize. In addition, there is a situation where the productivity of the target material 10 is reduced and the production cost is increased. Therefore, the heating time at the above heating temperature is preferably 40 hours or less, more preferably 20 hours or less, and further preferably 15 hours or less.

[0184] In this step, from the viewpoint of reliably oxidizing the target material 10 to the center portion, a multi-stage oxidation treatment may be performed at different heating temperatures.

[0185] <Finishing and joining to backing plate>

[0186] Thereafter, if necessary, the sintered body is ground, for example, to a size of 4500 mm 2 The target 10 of this embodiment is obtained by forming a disk-shaped target having a thickness of 3 mm or more, or polishing the surface to adjust the surface state. The target 10 is bonded to a backing plate made of Cu or the like via a bonding material such as In, Sn, or an alloy containing these metals, and is used as a sputtering target.

[0187] (3) Effect

[0188] According to this aspect, one or more of the following effects can be obtained.

[0189] (a) The target material 10 of this embodiment has the following three characteristics: density of 4.2 g / cm 3 The following characteristics: the characteristic that the Vickers hardness is 30 or more and 200 or less; and the characteristic that the area average grain size Nv is 3.0 μm or more. Thus, a target material 10 having a low density and being resistant to cracking can be obtained.

[0190] In addition, by making it low density (density 4.2g / cm 3 The target material 10 of the present invention (hereinafter referred to as the target material 10) can obtain a target material 10 in which the composition of O and K is the desired composition in the entire region of the target material 10 (in the entire region in the thickness direction and the in-plane direction of the target material 10). From this result, it can be seen that according to this method, the composition of O and K in the entire region is the desired composition and the target material 10 is resistant to cracking. Therefore, by sputtering film formation using the target material 10, a KNN film with high reliability having predetermined physical properties and predetermined characteristics can be reliably obtained.

[0191] (b) For the target material 10 of this embodiment, KNN sintered powder is prepared by the novel method of the above-mentioned steps A to C. Thus, KNN sintered powder with a large average primary particle size, for example, KNN sintered powder with an average primary particle size of 3.0 μm or more can be obtained. By subjecting such KNN sintered powder with a large average primary particle size to hot pressing sintering under predetermined conditions, a target material 10 having the above-mentioned three characteristics can be obtained.

[0192] (c) By separately making NaNbO 3 Powder and KNbO 3 powder, can increase the NaNbO 3 The primary firing temperature A during the production of powder. For example, K 2 CO 3 powder, Na2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder is fired once in an atmosphere containing O using an electric furnace or the like, and the primary firing temperature A can be made higher than the primary firing temperature in the conventional method of producing a fired powder containing K, Na, and Nb. Since the primary firing temperature A can be increased in this way, the obtained NaNbO 3 By preparing NaNbO with a large average primary particle size in step A 3 By using the powder, the target material 10 having the characteristic that the area average grain size Nv is 3.0 μm or more can be obtained reliably. As a result, the target material 10 having the above-mentioned three characteristics can be obtained reliably.

[0193] (d) In step B, adjust K 2 CO 3 Powder and Nb 2 O 5 The mixing ratio of the powder is used to produce KNbO with a large average primary particle size. 3 By making KNbO with a large average primary particle size 3 By using KNbO in step B, a target material 10 having a characteristic that the area average particle size Nv is 3.0 μm or more can be obtained reliably. As a result, a target material 10 having the above three characteristics can be obtained more reliably. 3 The composition of the powder is adjusted to be rich in K. 2 CO 3 Powder and Nb 2 O 5 The mixing ratio of the powder can more reliably obtain KNbO with a large average primary particle size. 3 Powder, for example, KNbO having an average primary particle size of 3.0 μm or more 3 As a result, the target material 10 having the above-mentioned three characteristics can be obtained more reliably.

[0194] (e) In steps A and B, since NaNbO with a large average primary particle size is produced, 3 Powder and KNbO 3 The target material 10 thus obtained may have a plurality of crystal grains observed on the sputtering surface 10s mainly including a plurality of NaNbO 3 Grains and multiple KNbO 3 Characteristics of crystal grains. In addition, the target 10 may have characteristics in which a Na-rich portion and a K-rich portion are dispersed on the sputtering surface 10 s.

[0195] It should be noted that, when hot pressing sintering is performed, it is also possible to use KNN sintered powder prepared as follows. That is, first, prepare K 2CO 3 powder, Na 2 CO 3 Powder and Nb 2 O 5 The starting material powders are then weighed to adjust the mixing ratio of the starting material powders so that the composition of the target material 10 finally obtained is the desired composition. 2 CO 3 powder, Na 2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder is fired once in an atmosphere containing O using an electric furnace or the like to obtain a fired product containing K, Na, and Nb ((K, Na)NbO 3 ). Thereafter, the obtained fired product is coarsely pulverized using a predetermined pulverizing mechanism, thereby obtaining fired powder ((K, Na)NbO 3 Powder). The powder was coarsely pulverized by a predetermined pulverizing mechanism to obtain KNN sintered powder. However, even when the KNN sintered powder obtained in this way was hot-pressed, a powder having a density of 4.2 g / cm 3 A target material having three characteristics: the following characteristics, the characteristic that the Vickers hardness is 30 or more and 200 or less, and the characteristic that the area average grain size Nv is 3.0 μm or more.

[0196] This is because, in such a method for producing KNN sintered powder, if the heating temperature in the primary sintering is lowered, it is impossible to obtain KNN sintered powder with an average primary particle size of 3.0 μm or more. When such KNN sintered powder is used for hot pressing sintering at the same temperature (sintering temperature) as in the above-mentioned step D, the density of the obtained KNN sintered body (target material) becomes high. In other words, it is impossible to obtain a KNN sintered body with a density of 4.2 g / cm 3 In addition, when hot pressing is performed using such KNN sintered powder at a temperature lower than the sintering temperature in the above-mentioned step D, a target cannot be formed with grains having a large average grain size. In other words, a target having a characteristic of an area average grain size Nv of 3.0 μm or more cannot be obtained.

[0197] On the other hand, in such a method for producing KNN calcined powder, if the heating temperature in the primary calcination is increased, KNN calcined powder having an average primary particle size of 3.0 μm or more can be obtained. However, the KNN calcined powder obtained by such a method becomes a calcined powder containing Na and Nb (NaNbO 3 powder) and sintered powder containing K and Nb (KNbO 3Therefore, when hot pressing sintering is performed using such KNN sintered powder at the same temperature as the sintering temperature in the above-mentioned step D, the density of the obtained target material becomes too high. That is, it is impossible to obtain a target material having a density of 4.2 g / cm 3 In addition, when hot pressing is performed using such KNN sintered powder at a temperature lower than the sintering temperature in the above-mentioned step D, a target having a Vickers hardness of 30 or more and 200 or less cannot be obtained.

[0198] On the other hand, in the present method, NaNbO 3 Powder and KNbO 3 powder, the prepared NaNbO 3 Powder and KNbO 3 The powders are mixed and calcined to produce KNN calcined powder. Thus, as described above, KNN calcined powder having an average primary particle size of 3.0 μm or more can be obtained. In addition, in the method of this embodiment, when producing KNN calcined powder (in the above-mentioned step C), NaNbO is intentionally not used. 3 Powder and KNbO 3 By using such KNN sintered powder and hot pressing it at the sintering temperature in the above-mentioned step D, a KNN sintered powder having a density of 4.2 g / cm 3 The target material 10 has the following three characteristics: a characteristic of having a Vickers hardness of 30 or more and 200 or less, and a characteristic of having an area average grain size Nv of 3.0 μm or more. In addition, in step C, by not making NaNbO 3 Powder and KNbO 3 The target material 10 also has a feature that the Na-rich portion and the K-rich portion are dispersed on the sputtering surface 10 s.

[0199] In addition, in the above-mentioned method, the sintering of the KNN sintered powder is carried out by hot pressing sintering, but it is also possible to consider using spark plasma sintering (hereinafter referred to as SPS) to carry out the sintering of the KNN sintered powder. However, in the case of sintering using SPS, the pressed powder body is prone to excessive densification. Therefore, it is not possible to obtain a density of 4.2 g / cm 3 The case of the target material 10 is as follows.

[0200] <Other aspects of the present invention>

[0201] Various aspects of the present invention have been described above in detail. However, the present invention is not limited to the above aspects, and various modifications can be made without departing from the spirit and scope of the present invention.

[0202] In the target 10 , at least one element (dopant) selected from the following group may be added as a dopant, for example, at a concentration of 5 at % or less, in addition to or instead of at least one element selected from Cu and Mn. As the dopant, at least one element selected from lithium (Li), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), bismuth (Bi), antimony (Sb), vanadium (V), In, tantalum (Ta), molybdenum (Mo), tungsten (W), chromium (Cr), Ti, zirconium (Zr), hafnium (Hf), scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), zinc (Zn), silver (Ag), iron (Fe), cobalt (Co), nickel (Ni), Al, silicon (Si), germanium (Ge), Sn, and gallium (Ga) can be exemplified. When a plurality of the above elements are added, the total concentration is 5 at% or less, and the amount of dopant added is usually 0.1 at% or more. In this case, in the above step C, as the starting raw material powder, a powder containing at least one dopant element selected from Li, Mg, Ca, Sr, Ba, Bi, Sb, V, In, Ta, Mo, W, Cr, Ti, Zr, Hf, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Zn, Ag, Fe, Co, Ni, Al, Si, Ge, Sn, Ga is further prepared, for example, a powder of a single substance of the element, a powder of an oxide containing the element, a powder of a composite oxide containing the element, and a powder of a compound containing the element that becomes an oxide by heating (e.g., a carbonate, an oxalate) is prepared, and NaNbO 3 Powder and KNbO 3 Just mix the powder.

[0203] Example

[0204] Hereinafter, experimental results confirming the effects of the above-mentioned aspects will be described; however, the present invention is not limited to the following Examples.

[0205] (Sample 1)

[0206] Will Na 2 CO 3 Powder and Nb 2 O 5 Powder is mixed in a prescribed ratio, and Na 2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder is heated at 1200℃ in an atmosphere containing O to produce NaNbO3 powder (step A). 2 CO 3 Powder and Nb 2 O 5 Powder is mixed in a prescribed ratio, and K 2 CO 3 Powder and Nb 2 O 5 The mixed powder of the powder was heated at 800°C in an atmosphere containing O to produce KNbO 3 In step B, KNbO 3 The composition of the powder is adjusted to be rich in K. 2 CO 3 Powder and Nb 2 O 5 The mixing ratio of KNbO powder produced in step B 3 K / Nb ratio of powder (KNbO 3 The ratio of K composition to Nb composition in the powder was 1.015. 3 Powder and KNbO 3 powder and CuO powder are mixed at a specified ratio to form NaNbO 3 Powder and KNbO 3 The mixed powder of the powder and the CuO powder was heated at 750°C in an atmosphere containing O to produce KNN sintered powder containing Cu as a dopant (step C). The pressure during sintering was set to 400 kgf / cm 2 The sintering temperature was set to 900°C, and the obtained KNN sintered powder was subjected to hot pressing sintering to produce a KNN sintered body (step D). The obtained KNN sintered body was subjected to heat treatment (oxidation treatment) at 800°C for 1 hour in an atmosphere containing O (step E). Thereafter, the surface of the KNN sintered body was subjected to prescribed processing such as grinding to obtain a disc-shaped KNN target with a thickness of 5 mm and a diameter of 300 mm (300 mmφ). The KNN target was set as sample 1.

[0207] In samples 2 to 29, the temperature in step A (primary sintering temperature A), the K / Nb ratio in step B (i.e., K 2 CO 3 Powder and Nb 2 O 5The mixing ratio of the powder), the temperature in step B (primary firing temperature B), the pressure in step D (sintering pressure), the temperature in step D (sintering temperature), whether step E is implemented, or the temperature in step E is changed as shown in Table 1. The other production steps and production conditions are the same as those of sample 1, and the targets of samples 2 to 29 are produced respectively. It should be noted that in the column of step E in Table 1, "0" means that step E is implemented, and "×" means that step E is not implemented.

[0208] In addition, in samples 30 to 33, the jig (sintering mold) used in step D was changed. The other production steps and production conditions were set to the same steps and conditions as sample 1, and targets of samples 30 to 33 of various sizes were produced. It should be noted that the target materials of samples 30 to 32 were disc-shaped, and the target material of sample 33 was a plate-shaped material with a rectangular main surface. The dimensions of the target materials of samples 30 to 33 are shown in Table 1.

[0209]

[0210] <About NaNbO produced in step A 3 Fans' comments>

[0211] The NaNbO prepared in samples 1 to 33 3 The results of the measurement of the average primary particle size of the powder are shown in Table 1. It should be noted that the "average diameter" in Table 1 is the average diameter of NaNbO obtained from the SEM image. 3 The average primary particle size of the powder, specifically, NaNbO 3 The median diameter D of the primary particles of the powder 50 .

[0212] In samples 1 to 4 and 7 to 33, NaNbO 3 The average primary particle size of the powder is 5.0 μm or more. From this result, it can be seen that by setting the temperature in step A to 1000° C. or more, NaNbO having an average primary particle size of 5.0 μm or more (8.0 μm or more in the example) can be obtained. 3 In addition, it can be seen that in samples 1 to 4, 7 to 33, NaNbO 3 The average primary particle size of the powder is larger than that of KNbO prepared in step B. 3 The average primary particle size of the powder.

[0213] In addition, NaNbO 3 The average primary particle size of the powder was 10.0 μm or more. From this result, it can be seen that by setting the temperature in step A to 1100° C. or more, NaNbO having an average primary particle size of 10.0 μm or more can be obtained. 3powder, that is, NaNbO with a large average primary particle size can be reliably obtained 3 pink.

[0214] It should be noted that NaNbO 3 The average primary particle size of the powder is less than 5.0 μm. From this result, it can be seen that if the temperature in step A is lower than 1000°C, the NaNbO 3 The situation of primary particles of powder.

[0215] In addition, it can be seen from Sample 6 that even when the temperature in Step A is higher than the temperature in Step B, if the temperature in Step A is lower than 1000° C., NaNbO may not be formed. 3 The average primary particle size of the powder is larger than that of the KNbO prepared in step B. 3 The average primary particle size of the powder.

[0216] <About KNbO produced in step B 3 Fans' comments>

[0217] The KNbO prepared in samples 1 to 33 3 The measurement results of the average primary particle size of the powder are shown in Table 1. It should be noted that the "K / Nb ratio" in Table 1 is the ratio of the KNbO 3 The ratio of K composition to Nb composition in the powder. In addition, the "average diameter" in Table 1 is the KNbO 3 The average diameter of the primary particles of the powder, specifically KNbO 3 The median diameter D of the primary particles of the powder 50 .

[0218] KNbO can be confirmed in samples 1 to 11, 13 to 17, and 19 to 33. 3 The average primary particle size of the powder is 3.0 μm or more (5.0 μm or more in the examples). This result shows that KNbO having an average primary particle size of 3.0 μm or more can be obtained by setting the K / Nb ratio to 1.005 or more. 3 It is also known that by setting the temperature in step B to 500°C or higher, KNbO having an average primary particle size of 3.0 μm or higher can be reliably obtained. 3 pink.

[0219] It should be noted that in sample 12, KNbO 3 The average primary particle size of the powder is less than 3.0 μm. From this result, it can be seen that if the K / Nb ratio is less than 1.005, the KNbO 3 The situation of primary particles of powder.

[0220] In addition, in sample 18, it can be confirmed that KNbO 3 The average primary particle size of the powder is less than 3.0 μm. From this result, it can be seen that even if the K / Nb ratio is 1.005 or more, if the temperature in step B is less than 500°C, the KNbO 3 The situation of primary particles of powder.

[0221] <Evaluation of target materials>

[0222] Physical property evaluations were performed on the density, Vickers hardness, average grain size, and composition of K, Na, and Nb of each sample (target material). In addition, evaluations were also performed on cracking of each sample.

[0223] (Evaluation of density)

[0224] The densities of the target materials of Samples 1 to 33 were measured using the following apparatus and method.

[0225] Device: ALFA MIRAGE electronic density meter MDS300

[0226] Test method: The density of a target material cut into a predetermined size was measured by the Archimedean method using the above-mentioned device.

[0227] (Evaluation of Vickers hardness)

[0228] The Vickers hardness of the target materials of Samples 1 to 33 was measured using the following apparatus, conditions, and method.

[0229] Equipment: Micro Vickers hardness tester HM-114 manufactured by Mitutoyo Corporation

[0230] Atmosphere: Atmospheric

[0231] Temperature: Room temperature (25°C)

[0232] Test force: 1.0kgf

[0233] Load application speed: 10μm / s

[0234] Hold time: 15 seconds

[0235] Measurement points: 5 points

[0236] Test method: This test is based on JIS R 1610. A Vickers indenter (a quadrangular pyramid indenter with a square bottom and two facing surfaces at an angle of 136 degrees) is used to calculate the Vickers hardness based on the test force when a pit is formed on the test surface and the pit surface area calculated from the diagonal length of the pit. The average of the measurement results at 5 points is calculated.

[0237] (Evaluation of average particle size)

[0238] The sputtering surfaces of the targets of Samples 1 to 33 were observed by EBSD, and the area average grain size Nv (μm) of a plurality of crystal grains observed on the sputtering surfaces was calculated using the following apparatus, conditions, and method.

[0239] Sample preparation: Performed by grinding method (polishing with water-resistant abrasive paper until there are no major scratches that interfere with the evaluation, and then polishing.)

[0240] Equipment: Ultra-high resolution analysis scanning electron microscope SU-70 manufactured by Hitachi High-Tech Co., Ltd.

[0241] EBSD detector manufactured by TSL Solutions Co., Ltd.

[0242] Analysis software: OIM Analysis Ver8 manufactured by TSLSolutions Co., Ltd.

[0243] Measurement magnification: 3000 times

[0244] Measurement area: 30μm×50μm

[0245] Step size: 0.06 μm

[0246] Grain boundary angle: 15°

[0247] Analysis method: In order to remove noise, a cleanup process was performed, and a grain boundary distribution map was made under the condition of a grain boundary angle of 15° (boundaries with a crystal orientation difference of more than 15° were considered grain boundaries), and the particle size was analyzed. In the presence of voids, etc., a threshold was set for the IQ (Image Quality) value. The area and particle size (equivalent circle diameter) of each particle were calculated using the Area Fraction method of EBSD, and the area average particle size was calculated. In addition, when calculating the particle size, in order to remove the parts and microcrystals that cannot be analyzed due to poor crystallinity as noise, particles larger than 0.20μm were used as the calculation object.

[0248] (Evaluation of the composition of K, Na, and Nb)

[0249] The composition of the target materials of samples 1 to 33 was measured by AAS for the molar content of K and Na, and by ICP-AES for the molar content of Nb, and the value of ([K] + [Na]) / [Nb] was calculated. It should be noted that [K], [Na], and [Nb] are the molar content of K atoms, the molar content of Na atoms, and the molar content of Nb atoms in the target, respectively. [K], [Na], and [Nb] were measured using the following apparatus, conditions, and methods.

[0250] Sample preparation: Each sample was cut into a size of 10 mm × 10 mm (× thickness 5 mm).

[0251] Equipment: Atomic absorption spectrometry (AAS) device Z-2300 manufactured by Hitachi High Technologies Co., Ltd. High-frequency inductively coupled plasma atomic emission spectrometry (ICP-AES) device PS3520VDDII manufactured by Hitachi High-Tech Science Co., Ltd.

[0252] Analysis method: After the cut samples were heated and decomposed with sulfuric acid, nitric acid, hydrofluoric acid and hydrochloric acid, they were heated and dissolved with dilute hydrogen peroxide and dilute hydrofluoric acid and the volume was fixed. Thereafter, the solution was subjected to AAS and ICP-AES to obtain the contents of K, Na and Nb in the sample and convert them into atomic ratios.

[0253] (Evaluation of rupture)

[0254] After step E (oxidation treatment), samples 1 to 33 were visually checked for the presence of cracks (including cracks and chips).

[0255] In addition, using each of the samples 1 to 4, 6 to 17, 20, 21, 23, and 25 to 33 in which no abnormal composition was observed and no cracks were observed after step E (oxidation treatment), a KNN film was sputtered by the following steps. Afterwards, each sample after sputtering was visually checked for cracks (including cracks and notches) and abnormal discharge traces.

[0256] As a substrate, a 4-inch diameter, 510 μm thick, (100) oriented surface with a 200 nm thick thermal oxide film (SiO 2 Thereafter, a Ti film (thickness 2 nm) as an adhesion layer, a Pt film (preferentially oriented along the (111) plane relative to the surface of the substrate, thickness 200 nm) as a lower electrode film, and a KNN film (diameter 4 inches, preferentially oriented along the (001) plane relative to the surface of the substrate, thickness 2 μm) as a piezoelectric film were sequentially formed on the thermal oxide film of the substrate by RF magnetron sputtering (using an RF plasma sputtering device).

[0257] The conditions for producing the adhesion layer and the lower electrode film were respectively as follows.

[0258] Substrate temperature: 300°C

[0259] Discharge power density: 13.5W / cm 2

[0260] Atmosphere: Ar atmosphere

[0261] Atmosphere pressure: 0.3Pa

[0262] Film making time: 5 minutes

[0263] The conditions for producing the KNN film were as follows.

[0264] Discharge power density: 2W / cm 2 Above and 5W / cm 2 The following specified discharge power density

[0265] Atmosphere: Ar+O 2 Mixed gas atmosphere

[0266] Atmosphere pressure: 0.3Pa

[0267] Ar / O 2 Voltage division ratio: 25 / 1

[0268] Temperature (substrate temperature): 600°C

[0269] Film forming speed: 1μm / hr

[0270] These evaluation results (measurement results) are shown in Table 2. In addition, the "(K+Na) / Nb composition" in Table 2 is a value of ([K]+[Na]) / [Nb].

[0271]

[0272] In samples 1 to 4, 7 to 11, 13 to 17, 20, 23, and 25 to 33, it was confirmed that the density was 4.2 g / cm 3 The target materials were as follows: 1.5 μm, 2.5 μm, 0.2 μm, 0.4 μm, 1.2 μm, 0.6 μm, 0.7 μm, 1.2 μm, 0.8 μm, 1.4 μm, 0.9 μm, 1.2 μm, 0.9 μm, 1.3 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 1.9 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 1.9 μm, 1.2 μm, 1.4 μm, 1.8 μm, 1.6 μm, 1.8 μm, 1.9 μm, 1.4 μm, 1.8 μm, 1.9 μm, 1.4 μm, 1.8 μm, 1.4 μm, 1.6 μm, 1.8 μm, 1.9 μm, 1.4 μm, 1.8 μm, 1.4 μm, 1.8 μm, 1.4 μm, 1.8 μm, 1.9 μm, 1.4 μm, 1.4 μm, 1.8 μm, 1.4 μm, 1.4 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 ...4 μm, 1.4 μm, 1.4 μm, 1.4 μm, 1.4 μm,

[0273] Furthermore, it can be seen from Samples 30 to 33 that a target material that is resistant to cracking despite having a low density can be obtained regardless of the size and planar shape of the target material.

[0274] In addition, the target materials of samples 1 to 4, 7 to 11, 13 to 17, 20, 23, and 25 to 33 were cut in the thickness direction, and their cut surfaces (longitudinal sections) were visually observed. Figure 3 (a) shows the schematic structure of the cut surface of sample 1. Figure 3 (b) shows a photograph of the fractured surface of sample 1. Figure 3 (a) and Figure 3 (b) It can be confirmed that in sample 1, the surface (upper surface and lower surface) and the interior (center) are white, that is, the entire region is white. This indicates that sample 1 is fully oxidized to the center, that is, the composition of O in the entire region is the desired composition. Similarly, the longitudinal sections of samples 2 to 4, 7 to 11, 13 to 17, 20, 23, and 25 to 33 can also be confirmed to be white in the entire region. From these results, it can be seen that in samples 1 to 4, 7 to 11, 13 to 17, 20, 23, and 25 to 33, even when the oxidation treatment is performed at a low temperature of less than 1000°C (even if the temperature in step E is less than 1000°C), it can be fully oxidized to the center of the target.

[0275] In addition, in all of Samples 1 to 4, 7 to 11, 13 to 17, 20, 23, and 25 to 33, it was confirmed that the value of ([K] + [Na]) / [Nb] was greater than 1.0.

[0276] In addition, it can be seen from Sample 25 that by setting the density to 4.2 g / cm 3 Even if step E (oxidation treatment) is not performed, a target material having a low density but resistant to cracking may be obtained. However, from the viewpoint of reliably obtaining a target material having a desired composition of O in all regions, it is preferred to perform step E.

[0277] It should be noted that in samples 5, 6, 12, and 18, the area average particle size Nv was confirmed to be less than 3.0 μm. This result shows that the NaNbO 3 In the case of the average primary particle size of the powder, the KNbO 3 In the case of the average primary particle size of the powder, there are cases where the target material area average particle size Nv cannot be made to be 3.0 μm or more. In addition, in samples 5 and 18, cracks can be confirmed after the completion of step E, and in samples 6 and 12, cracks (cracks) and abnormal discharge can be confirmed after the implementation of sputtering film formation. From these results, it can be seen that if the target material area average particle size Nv is less than 3.0 μm, cracks are likely to occur during the preparation of the target material and during sputtering film formation.

[0278] In samples 19 and 22, it was confirmed that the Vickers hardness was less than 30. From this result, it can be seen that the pressure in step D was less than 100 kgf / cm 2In the case of the temperature in step D being lower than 800°C, the Vickers hardness may not be higher than 30. In addition, in samples 19 and 22, cracks were confirmed to occur after step E. From these results, it can be seen that if the Vickers hardness of the target is lower than 30, cracks are likely to occur during the preparation of the target and during sputtering film formation.

[0279] In samples 21 and 24, it was confirmed that the Vickers hardness was greater than 200. From this result, it can be seen that in order to obtain a target material with a Vickers hardness greater than 200, the pressure in step D needs to be greater than 500 kgf / cm 2 , the temperature in step D was set to be higher than 1150°C. In addition, it was also confirmed that the density of samples 21 and 24 was higher than 4.2 g / cm 3 .

[0280] Furthermore, the target material of the sample 21 was cut in the thickness direction, and the cut surface (longitudinal section) was visually observed. Figure 4 (a) shows a schematic diagram of the fractured surface of sample 21. Figure 4 (b) shows a photograph of the fractured surface of sample 21. Figure 4 (a) and Figure 4 (b) It can be confirmed that in sample 21, the surface (upper and lower surfaces) is white, while the interior (center) is gray, navy blue, and black. This indicates that in sample 21, although the surface is oxidized, the center is in a state with less oxygen (i.e., unoxidized state). From this result, it can be seen that if the pressure in step D is high, the density is greater than 4.2 g / cm 3 In this case, if the temperature in step E is a low temperature of less than 1000°C, the target may not be sufficiently oxidized to the center portion. That is, it is known that the composition of O cannot be made the desired composition in the entire region of the target. In addition, in sample 21, cracks and abnormal discharges were also confirmed after the sputtering film was formed.

[0281] In addition, in sample 24, it can be confirmed that the composition of the surface is a K-deficient composition. From this result, it can be seen that if the temperature in step D is higher than 1100°C, K in a part of the target material will volatilize, and there may be a case where the composition of K cannot be made into the desired composition in the entire region of the target material. In addition, in sample 24, it can be confirmed that cracks are generated after the completion of step E. From this result, it can be seen that when the temperature in step D is high, cracks may occur during the preparation of the target material.

[0282] <Preferred Embodiments of the Invention>

[0283] Preferred embodiments of the present invention are described below.

[0284] (Note 1)

[0285] According to one embodiment of the present invention, there is provided a sputtering target material comprising a sintered body containing oxides of potassium, sodium, niobium, and oxygen.

[0286] Density: 4.2g / cm 3 the following.

[0287] Thereby, a target material in which the compositions of O and K are desired compositions in all regions can be obtained.

[0288] (Note 2)

[0289] According to another aspect of the present invention, there is provided a sputtering target.

[0290] It is composed of a sintered body containing oxides of potassium, sodium, niobium and oxygen.

[0291] Vickers hardness is 30 or more and 200 or less,

[0292] The area average grain size of a plurality of crystal grains observed on the sputtered surface was 3.0 μm or more.

[0293] Thereby, a target material having high mechanical strength can be obtained.

[0294] (Note 3)

[0295] According to another aspect of the present invention, there is provided a sputtering target.

[0296] It is composed of a sintered body containing oxides of potassium, sodium, niobium and oxygen.

[0297] Density: 4.2g / cm 3 the following,

[0298] Vickers hardness is 30 or more and 200 or less,

[0299] The area average grain size of a plurality of crystal grains observed on the sputtered surface was 3.0 μm or more.

[0300] Thereby, it is possible to obtain a target material in which the compositions of O and K are desired in all regions and which has high mechanical strength.

[0301] (Note 4)

[0302] According to the target material according to Supplementary Note 2 or 3, it is preferred that the area average grain size is a value calculated from an electron backscatter diffraction (EBSD) image using an Area Fraction method.

[0303] (Note 5)

[0304] The target material according to any one of appendices 1 to 4, wherein the area of ​​the main surface is preferably 4500 mm 2 above.

[0305] (Note 6)

[0306] The target material according to any one of Supplementary Notes 1 to 5, wherein the target material preferably contains at least one element selected from copper and manganese as a dopant at a concentration of 0.1 at % to 2.0 at %.

[0307] (Note 7)

[0308] The target material according to any one of Supplementary Notes 1 to 6, wherein the plurality of crystal grains observed on the sputtering surface preferably mainly include: a plurality of crystal grains containing an oxide containing sodium and niobium; and a plurality of crystal grains containing an oxide containing potassium and niobium.

[0309] (Note 8)

[0310] The target material according to any one of Supplementary Notes 1 to 7, wherein the portion having a high sodium content (sodium-rich portion) and the portion having a high potassium content (potassium-rich portion) are preferably dispersed on the sputtering surface.

[0311] (Note 9)

[0312] A target material according to any one of Appendixes 1 to 8, wherein when the molar content of potassium atoms in the sintered body is set to [K], the molar content of sodium atoms is set to [Na], and the molar content of niobium atoms is set to [Nb], the value of ([K] + [Na]) / [Nb] is preferably greater than 1.0.

[0313] (Note 10)

[0314] According to another aspect of the present invention, there is provided a sputtering target comprising:

[0315] The sputtering target according to any one of appendices 1 to 9, and

[0316] A backing plate bonded to the sputtering target.

[0317] (Note 11)

[0318] According to another aspect of the present invention, there is provided a sputtering target.

[0319] It is composed of a sintered body containing oxides of potassium, sodium, niobium and oxygen.

[0320] The sputtering target was bonded to a backing plate via a bonding material to prepare a sputtering target, and the sputtering target was installed in an RF plasma sputtering device. In a mixed gas atmosphere of argon and oxygen, the discharge power density was set to 2.0 W / cm 2In the above, a process for manufacturing a piezoelectric film containing potassium, sodium, niobium and oxygen is performed, and when the above sputtering target is observed after the process for manufacturing the above piezoelectric film is performed until the cumulative film thickness of the above piezoelectric film is greater than 50 μm, no cracks are generated. Here, the so-called "no cracks" means that no cracks that may cause abnormal discharge are generated when sputtering is performed at the above discharge power density.

[0321] (Note 12)

[0322] According to another aspect of the present invention, there is provided a method for manufacturing a sputtering target.

[0323] A method for producing a sputtering target material composed of a sintered body containing oxides of potassium, sodium, niobium and oxygen, the method comprising:

[0324] (a) a step of mixing a raw material powder containing a compound including sodium and a raw material powder containing a compound including niobium at a predetermined ratio, and heating the mixture in an oxygen-containing atmosphere to produce a calcined powder containing sodium and niobium;

[0325] (b) a step of mixing a raw material powder containing a compound including potassium and a raw material powder containing a compound including niobium at a predetermined ratio, and heating the mixture in an oxygen-containing atmosphere to produce a calcined powder containing potassium and niobium;

[0326] (c) a step of mixing the calcined powder prepared in (a) and the calcined powder prepared in (b) at a predetermined ratio, and heating (calcining) the mixture in an oxygen-containing atmosphere to prepare a calcined powder containing potassium, sodium and niobium; and

[0327] (d) a step of applying a predetermined pressure to the calcined powder produced in (c) to form a green compact, and heating the green compact to form a sintered body,

[0328] The heating temperature in (a) is made higher than the heating temperature in (b).

[0329] (Note 13)

[0330] According to the manufacturing method described in Appendix 12, it is preferred that in (c), the above-mentioned sintered powder produced in (a), the above-mentioned sintered powder produced in (b) and a powder containing at least one element selected from copper and manganese are mixed in a prescribed ratio to produce a sintered powder containing potassium, sodium and niobium and containing at least one element selected from copper and manganese as a dopant.

[0331] (Note 14)

[0332] The production method according to Appendix 12 or 13, preferably further comprising the step of (e) heat treating the sintered body in an oxygen-containing atmosphere at a temperature of 500° C. to 1100° C. for 1 hour or more after (d).

[0333] (Note 15)

[0334] The production method according to any one of Appendixes 12 to 14, wherein the heating temperature in (a) is preferably a temperature at which the average diameter of primary particles of the calcined powder containing sodium and niobium is larger than the average diameter of primary particles of the calcined powder containing potassium and niobium produced in (b).

[0335] (Note 16)

[0336] According to the production method described in Appendix 15, it is preferred that the above-mentioned average diameter of the primary particles of the above-mentioned sintered powder containing sodium and niobium and the above-mentioned average diameter of the primary particles of the above-mentioned sintered powder containing potassium and niobium are values ​​read and calculated from an image observed at a magnification of 2000 to 5000 times with a scanning electron microscope (SEM).

[0337] (Note 17)

[0338] The production method according to any one of Supplementary Notes 12 to 16, wherein the heating temperature in (a) is preferably a temperature at which the average diameter of primary particles of the calcined powder containing sodium and niobium becomes 5.0 μm or more, more preferably 10.0 μm or more.

[0339] (Note 18)

[0340] The production method according to any one of Appendixes 12 to 17, wherein the heating temperature in (a) is preferably 1000° C. or higher.

[0341] (Note 19)

[0342] The production method according to any one of Appendixes 12 to 18, wherein the mixing ratio of the raw material powder containing the compound containing potassium and the raw material powder containing the compound containing niobium is preferably adjusted in (b) so that the average diameter of the primary particles of the calcined powder containing potassium and niobium is 3.0 μm or more, preferably 5.0 μm or more.

[0343] (Note 20)

[0344] According to the production method described in Supplementary Note 19, preferably, the average diameter of the primary particles of the calcined powder containing potassium and niobium is a value calculated by reading from an image observed by a scanning electron microscope (SEM) at a magnification of 2000 to 5000 times.

[0345] (Note 21)

[0346] The production method according to any one of Appendixes 12 to 20, wherein the mixing ratio of the raw material powder containing a compound containing potassium and the raw material powder containing a compound containing niobium is preferably adjusted in (b) so that the composition of the calcined powder containing potassium and niobium is a composition rich in potassium.

[0347] (Note 22)

[0348] According to the production method described in Appendix 21, it is preferred that in (b), the mixing ratio of the raw material powder containing the compound containing potassium and the raw material powder containing the compound containing niobium is adjusted so that the ratio of the composition of potassium to the composition of niobium (K / Nb) in the calcined powder containing potassium and niobium is 1.005 or more.

[0349] (Note 23)

[0350] A production method according to any one of Appendixes 12 to 22, wherein in (c), the mixing is preferably carried out under the condition that the average diameter of primary particles of the mixed powder produced by mixing the calcined powder produced in (a) and the calcined powder produced in (b) is 3.0 μm or more, preferably 5.0 μm or more.

[0351] (Note 24)

[0352] The production method according to any one of Supplementary Notes 12 to 23, wherein in (c), preferably, at least one of pulverizing a mixed powder produced by mixing the calcined powder produced in (a) with the calcined powder produced in (b) or pulverizing the calcined powder containing potassium, sodium and niobium is performed,

[0353] The pulverization is performed under the condition that the average diameter of primary particles of the mixed powder or the calcined powder after pulverization is 3.0 μm or more, preferably 5.0 μm or more.

[0354] (Note 25)

[0355] The production method according to Appendix 23 or 24, wherein the average diameter of the primary particles of the mixed powder or the calcined powder is preferably a value read and calculated from an image observed by a scanning electron microscope (SEM) at a magnification of 2000 to 5000 times.

[0356] Description of Reference Numerals

[0357] 10 targets, 10s sputtering surface.

Claims

1. A sputtering target, It is composed of a sintered body containing oxides of potassium, sodium, niobium and oxygen. Density: 4.2g / cm 3 the following, Vickers hardness is 30 or more and 200 or less, The area average grain size of a plurality of crystal grains observed on the sputtered surface was 3.0 μm or more.

2. The sputtering target according to claim 1, wherein the area of ​​the main surface is 4500 mm 2 above.

3. The sputtering target according to claim 1, wherein: At least one element selected from copper and manganese is contained as a dopant at a concentration of 0.1 at % to 2.0 at %.

4. The sputtering target according to claim 1, wherein: The plurality of crystal grains observed on the sputtering surface mainly include: a plurality of crystal grains containing an oxide containing sodium and niobium; and a plurality of crystal grains containing an oxide containing potassium and niobium.

5. The sputtering target according to claim 1, wherein: The sputtering surface is dotted with a portion having a high sodium content and a portion having a high potassium content.

6. The sputtering target according to any one of claims 1 to 5, wherein When the number of moles of potassium atoms contained in the sintered body is [K], the number of moles of sodium atoms is [Na], and the number of moles of niobium atoms is [Nb], the value of ([K] + [Na]) / [Nb] is greater than 1.

0.

7. A method for manufacturing a sputtering target, A method for producing a sputtering target composed of a sintered body containing oxides of potassium, sodium, niobium and oxygen, the method comprising: (a) a step of mixing a raw material powder containing a compound including sodium and a raw material powder containing a compound including niobium at a predetermined ratio, and heating the mixture in an oxygen-containing atmosphere to produce a calcined powder containing sodium and niobium; (b) a step of mixing a raw material powder containing a compound including potassium and a raw material powder containing a compound including niobium at a predetermined ratio, and heating the mixture in an oxygen-containing atmosphere to produce a calcined powder containing potassium and niobium; (c) a step of mixing the calcined powder prepared in (a) and the calcined powder prepared in (b) at a predetermined ratio and calcining the mixture in an oxygen-containing atmosphere to prepare a calcined powder containing potassium, sodium and niobium; and (d) a step of applying a predetermined pressure to the calcined powder produced in (c) to form a green compact, and heating the green compact to form a sintered body. The heating temperature in (a) is made higher than the heating temperature in (b).

8. The method for producing a sputtering target according to claim 7, wherein: In (c), the sintered powder prepared in (a), the sintered powder prepared in (b) and a powder containing at least one element selected from copper and manganese are mixed in a predetermined ratio to prepare a sintered powder containing potassium, sodium and niobium and containing at least one element selected from copper and manganese as a dopant.

9. The method for manufacturing a sputtering target according to claim 7, wherein: After performing step (d), the method further comprises the step of (e) heat-treating the sintered body in an oxygen-containing atmosphere at a temperature of 500° C. to 1100° C. for 1 hour or more.

10. The method for manufacturing a sputtering target according to claim 7, wherein: The heating temperature in (a) is a temperature at which the average diameter of primary particles of the calcined powder containing sodium and niobium is larger than the average diameter of primary particles of the calcined powder containing potassium and niobium produced in (b).

11. The method for manufacturing a sputtering target according to claim 7, wherein: The heating temperature in (a) is a temperature at which the average diameter of primary particles of the calcined powder containing sodium and niobium becomes 5.0 μm or more.

12. The method for manufacturing a sputtering target according to claim 7, wherein: The heating temperature in (a) is 1000° C. or higher.

13. The method for manufacturing a sputtering target according to claim 7, wherein: In (b), the mixing ratio of the raw material powder containing the compound containing potassium and the raw material powder containing the compound containing niobium is adjusted so that the average diameter of primary particles of the calcined powder containing potassium and niobium is 3.0 μm or more.

14. The method for manufacturing a sputtering target according to claim 7, wherein: In (b), the mixing ratio of the raw material powder containing the compound containing potassium and the raw material powder containing the compound containing niobium is adjusted so that the composition of the calcined powder containing potassium and niobium is a composition rich in potassium.

15. The method for producing a sputtering target according to claim 14, wherein: In (b), the mixing ratio of the raw material powder containing the compound containing potassium and the raw material powder containing the compound containing niobium is adjusted so that the ratio of the composition of potassium to the composition of niobium in the fired powder containing potassium and niobium is 1.005 or more.

16. The method for manufacturing a sputtering target according to claim 7, wherein: In (c), the mixing is performed under the condition that the average diameter of primary particles of the mixed powder prepared by mixing the calcined powder prepared in (a) and the calcined powder prepared in (b) is 3.0 μm or more.

17. The method for manufacturing a sputtering target according to claim 7, wherein: In (c), at least one of pulverizing a mixed powder prepared by mixing the calcined powder prepared in (a) with the calcined powder prepared in (b) or pulverizing the calcined powder containing potassium, sodium and niobium is performed. The pulverization is performed under the condition that the average diameter of primary particles of the mixed powder or the calcined powder after pulverization is 3.0 μm or more.

Citation Information

Patent Citations

  • Piezoelectric thin film element and piezoelectric thin film device

    JP2011146623A